Statistical Convergence of Order for Difference Sequences - Altin, Y.; Altinok, H.; Colak, R. (Natl Inquiry Services Centre Pty Ltd, 2015)
In this paper the concepts of (m)(v)-statistical convergence of order and strong (p, (m))-Ces`aro summability of order are introduced for sequences of complex (or real) numbers. Some relations between the (m)(v)-statistical convergence of order and strong (p, (m)(v))-Ces`aro summability of order are given. Also some relations between the space (p) ((m)(v), f) and S ((m)(v)) are examined.
Keywords: Sequences; statistical convergence; Ces`aro summability